Pengaruh Suhu terhadap Perkembangan Pradewasa Parasitoid Eriborus argenteopilosus Cameron (Hymenoptera: Ichneumonidae) - Nelly, Novri; Habazar, Trimurti; Syahni, Rahmat; Buchori, Damayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
Temperature effect on development time of the preadult parasitoid Eriborus argenteopilosus Cameron(Hymenoptera: Ichneumonidae) were studied to know development time, degree days and survival rate.Crocidolomia pavonana (Fabricius)(Lepidoptera: Pyralidae) larvae was exposed to E. argenteopilosus female andreared at four different temperatures i.e 160C, 200C, 250C and 300C. Data were analyzed using anova and linearregression to calculate degree day. At 200C E. argenteopilosus showed the highest degree day and survival rate(18.67 %), while at 300C nothing adult parasitoid emergenced. Degree day to development time of parasitoid attemperature 200C i.e fase egg-adult: 300.05; egg-pupae 173.35; pupae-adult 171.